The concept of health literacy in health promotion - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula (Journal of Education, Health and Sport, 2017)
Health literacy is still a little known issue in Poland. It is a very complex concept, because it covers all the skills, competences, knowledge, and ways of acquiring information in the broadly understood area of health. But the health literacy is not one of the key elements of health promotion. Diagnosis of the health literacy level of a given population seems a prerequisite for effective health education and prevention activities.